Hysteroscopic vaginoscopy. An additional diagnostic tool for recto-vaginal deep infiltrating endometriosis. Issue 2 (June 2021) - Zizolfi, Brunella; Foreste, Virginia; Di Spiezio Sardo, Attilio; Giampaolino, Pierluigi; Gencarelli, Annarita; Carugno, Jose; Bifulco, Giuseppe
Endometriosis is the presence of endometrial tissue outside the uterine cavity. Rectovaginal infiltration is present in 5% to 25% of the patients diagnosed with endometriosis. Accurate diagnosis is imperative for adequate counseling. Hysteroscopic vaginoscopy allows the inspection of the posterior vaginal fornix, not only providing better visualization of the area due to image magnification, but also allowing to obtain biopsy providing pathologic confirmation. We report the case of a 49-year-old nulliparous patient with long history of severe dysmenorrhea, deep dyspareunia and debilitating chronic pelvic pain not responding to medical treatment. On physical exam, recto-vaginal tender nodularity was palpated. Vaginal ultrasound and magnetic resonance imaging confirmed the presence of the nodular formation extending up to the rectum. In-office vaginoscopy revealed a perforated bulge on the uterine cervix, mimicking a double cervix. A biopsy of the nodule confirmed the presence of endometrial tissue, confirming the diagnosis of endometriosis. Patient underwent total hysterectomy with excision of deep infiltrating endometriosis which required segmental bowel resection with diverting loop colostomy. The final pathology confirmed the diagnosis of deep infiltrating endometriosis.